Settlement and Capacity Analysis of Land Support Development on Flyover in Large City; Pekanbaru, Indonesia - Husnul Kausarian; evan trionaldi; taufan Khalif Arrahman; dewandra bagus eka putra; Batara (Journal of Geoscience, Engineering, Environment, and Technology, 2020)
The study area located on the street of Soebrantas to Soekarno Hatta Street, with the coordinate position of 0 ° 30 ' 0.79 "N 101 ° 24 ' 57.88 "E - 0 ° 30 ' 0.16 "N 101 ° 24 ' 53.17 "E in Pekanbaru City, Indonesia. The development that will Conduct flyovers in this area became the basis of this research. The main study of this research is to find out how an Atterberg's boundaries, compressibility, and the likelihood of a ground decline in drill 1 use the value of N SPT to match with the purpose of this study. Which is (1) to know the large grain size of soil samples, (2) Knowing the value of the liquid limit, the plastic boundary, and the plastic index of the soil samples, (3) Knowing the possibility of land degradation in the research area, (4) Power capacity analysis of ground support (5) Knowing the decline of modeling using the Plaxis 2D method (6) knows the relationship of decreasing values based on NSPT and Plaxis (7) Knowing the relationship of sieve analysis and Attaberg limit with decreased results. Methods of data retrieval have done with soil testing in the field and soil testing in the laboratories. A comprehensive analysis of the grain has done with sieve analysis. Plastic boundary, liquid, and plastic boundary indices with method Attaberg limit. Decreased analysis and Power capacity analysis of ground support with NSPT value tests.